Teaching Histology Using Digital Slides in a Virtual Classroom (Delta Medical College Journal, 2025)
In the Phase-I of MBBS programme in Bangladesh, anatomy teachers have been using glass slides and standard microscopes along with a brief review of the lectures with projection slides during practical education and training in histology in all medical colleges for decades. However, during the COVID-19 pandemic days, due to closure of all medical colleges, medical education embraced virtual platforms. We tried to build a repository of digital histology slides from our collections in histology laboratory and many free web digital sources; we also adapted our lesson plans that fit online platform. Digital images (derived from microscopic glass slides and other web-based resources) shown on the computer screen had panning and zooming capabilities that simulates moving the stage and the low to high power magnification of an optical microscope. Each digital image had also a thumbnail image from which the students could always refer to when viewing the digital slides at a higher magnification for proper orientation of histologic sections. Digital imaging technology was involved there to acquire, manage, and analyze high-resolution digital images of tissue samples on slides. A revolutionary conversion happened in teaching histology from using traditional microscopy on glass slides to digital slides (first ever in our country); digital slides can be viewed, stored, and analyzed using computerized systems anytime, anywhere. Integration of digital technologies in virtual classroom into histology teaching and learning (in anatomy curriculum) allowed teachers and students to experience numerous benefits, e.g., enhanced and active learning, more accessibility, reduction in time and resource consumption, and online collaboration. However, some of the challenges we faced are excess time and efforts, required technical skills, infrastructure and logistic support from the institutions, and motivation among teachers and students.Delta Med Col J. Jul 2022;10(2): 77-82